Building a Moderate Generation through Inclusive Education: A Case Study in Semi-Modern Islamic Boarding Schools - Dwi Istiyani; Karnadi Karnadi; Nasikhin Nasikhin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study addresses the urgent need to strengthen inclusive character education in Islamic boarding schools as a response to rising religious intolerance and identity-based exclusivism in Indonesia. Focusing on Pabelan Islamic Boarding School in Magelang, Indonesia, the research employs a qualitative case study design, using participatory observation and in-depth interviews with ustadz, managers, and students. Data were analyzed thematically following the Miles and Huberman model and validated through source triangulation and member checking. Findings reveal four key strategies: integration of national values into the curriculum, inter-mazhab tolerance, non-violent discipline, and respect for local culture-collectively fostering a politically, religiously, psychosocially, and culturally inclusive environment. Students’ responses fell into three patterns: active acceptance, selective adaptation, and passive resistance, with most embracing inclusivity as aligned with rahmatan lil ‘alamin. Despite challenges; structural (limited infrastructure), cultural (homogeneous dominance), and pedagogical (conventional methods), the pesantren demonstrates strong potential as an agent of religious moderation. Theoretically, this study contributes to the discourse on Islamic education by repositioning inclusivity not as a modern import but as an essential, indigenous dimension of Islamic epistemology, thereby expanding the application of character education frameworks within faith-based institutions in pluralistic societies.